2018
DOI: 10.1093/cid/cix956
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Viral Transfer During Doffing of Ebola-Level Personal Protective Equipment in a Biocontainment Unit

Abstract: Among experienced HCWs, structured, observed doffing using ABHR protected against hand contamination with enveloped virus. Nonenveloped virus was infrequent on hands and scrubs but common on inner gloves, suggesting that inner gloves, but not necessarily ABHR, protect against hand contamination. Optimizing doffing protocols to protect against all types of viruses may require reinforcing careful handling of scrubs and good glove/hand hygiene with effective agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 30 publications
(43 reference statements)
1
41
0
1
Order By: Relevance
“…[35] Hands-on training can provide real-time feedback to correct behaviors in the moment with observer interventions or surrogates for contamination. [36,37] In this sample, skills maintenance training was limited and primarily occurred at ETCs. A barrier identified was debate over the appropriate frequency of training, though surveyed trainees who wanted refresher training, wanted it to occur 1-2 times annually.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Hands-on training can provide real-time feedback to correct behaviors in the moment with observer interventions or surrogates for contamination. [36,37] In this sample, skills maintenance training was limited and primarily occurred at ETCs. A barrier identified was debate over the appropriate frequency of training, though surveyed trainees who wanted refresher training, wanted it to occur 1-2 times annually.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have utilized both FP and MS2 as surrogate markers, some have also reported higher rates of FP compared to MS2 detections. 17,31 Others have reported similar detection rates 19,32 or more frequent MS2 detections. 21 This lack of agreement may indicate that neither marker performs significantly 8 room-exit observations were missing because room exit could not be observed.…”
Section: Discussionmentioning
confidence: 89%
“…Debate continues over whether UV-fluorescent markers or various viral surrogates are best-suited for testing PPE. [14][15][16] However, UV-fluorescence has advantages of both cost and the training benefit of visual reinforcement of contamination, which was a key consideration for this work. The method aimed to provide realistic exposure events in terms of quantity and means of contamination.…”
Section: Limitationsmentioning
confidence: 99%